Musical Phenomenon in the Traditional Art of Alee Tunjang in Aceh - Rahman, Surya; Denada, Berlian; Rozak, Abdul (Universitas Negeri Medan, 2023)
Alee Tunjang is an art form originating from North Aceh Regency that consists of melodic and rhythmic music elements. The form of this art instrument is in the form of vocals that chant verses, and mortar beaten by alu/alee in the form of percussion rhythms with six sound colors. These two types of musical instruments form a distinctive musical fabric in the presentation of the performance, where melodic and rhythmic instruments are played not only as the main melody and melodic musical accompaniment, but the two elements become inseparable, as evidenced by the musical fills of Alee Tunjang that alternate and complement each other. The purpose of this research is to analyze the musical phenomena found in the art of Alee Tunjang. The method in this research uses a qualitative approach, with data collection techniques: literature review, observation, interview, and documentation. Alee Tunjang's music is divided into three sections, namely: Saleum, Kisah, and Lani, which consists of one vocal player and five lesung players, each with a constant rhythm and repetition. The tempo and rhythm are similar in all parts of the Alee Tunjang song/chapter. The difference in rhythm and cadence is found in the lesung 4th instrument which plays the tung sound color by playing a pattern on a different weak beat in each part of the song/chapter of Alee Tunjang.